Effects of a Mortgage Interest Rate Subsidy: Evidence from Colombia - Marc Hofstetter; Jorge Tovar; Miguel Urrutia (Inter-American Development Bank (IDB), 2011)
Government intervention in the construction sector as a way to boost the economy has been a constant in Colombia for the past 90 years. This paper explicitly tests the impact of the most recent of such interventions: a subsidy to the mortgage interest rate. The results show that the subsidy boosted mortgage loans by around 38 percent. However, it is also found that real interest rates went up by 1. 09 percent, i. e. , there has been an incomplete pass-through of the subsidy to the consumer. The pass-through of this instance of intervention is estimated to be in the range of 65 percent to 74 percent.
Keywords: N96; R21; R28; 330